Influence of Financial Literacy, Herding Behavior, and Risk Perception on Financial Behavior: Case Study in West Java, Indonesia - Hidayat, Gustina; Anwar, Mokhamad; Affandi, Azhar (International Journal of Business, Law, and Education, 2024)
This study investigates the influence of financial literacy, herding behavior, and risk perception on financial behavior in West Java, Indonesia, while examining the moderating role of financial literacy. Employing a quantitative approach, data were collected from 400 respondents through structured questionnaires and analyzed using Structural Equation Modeling (SEM). The results reveal that financial literacy significantly enhances financial behavior, mitigates the adverse effects of herding behavior, and strengthens the positive impact of risk perception. Herding behavior negatively affects financial behavior, while risk perception has a positive influence. The findings highlight the crucial role of financial literacy in promoting informed and independent financial decision-making, underscoring the need for targeted financial education initiatives. These insights provide valuable implications for policymakers, financial institutions, and educators aiming to improve financial well-being in Indonesia.